ANALISIS TINDAK TUTUR LOKUSI, ILOKUSI, DAN PERLOKUSI PADA FILM “PAPA MAAFIN RISA” - Tuti Hidayah; Rochmat Tri Sudrajat; Dida Firmansyah (IKIP Siliwangi, 2020)
language. When someone speaks, then there is an interlocutor who will give a response to his speech. the formulation of the problem to be conveyed is analyzing speeches and speech acts. The purpose of this study is to describe each of the utterances that contain locus, illocutionary, and percocutionary events from the character in the film